Physiological Impact Of Aerobic Exercise During Fasting On Inflammatory Risk Factors In Obese Women - Maulida Kurniawati; Sugiharto Sugiharto; Desiana Merawati; Adi Pranoto (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Physical exercise during fasting is an interesting therapeutic agent in preventing increased inflammation in obesity. Therefore, this study aims to prove the physiological impact of a combination of physical exercise and fasting on inflammatory risk factors in obese women. This research involved 18 obese women as research subjects who met the predetermined criteria and were then randomly selected. Subjects were divided into 2 groups: a control group (K1; n = 9) and a group that combined physical exercise and fasting (K2; n = 9). Physical exercise is done aerobically using a treadmill for 40 minutes at moderate intensity while fasting is done intermittently: fasting for 16 hours, followed by not fasting for 8 hours. The combination of physical exercise and fasting was carried out for 2 weeks. Blood samples were taken to measure the risk of inflammation, using the CRP biomarker, from the cubital vein in as much as 4 mL, which was carried out before and after treatment. Data analysis used a paired sample t-test with a significance level of 5%. Based on the research results, there are significant differences. The level of CRP reduction between the treatment and control groups (p ≤ 0.05). Based on the results of this research, physiological evidence shows that aerobic exercise during intermittent fasting reduces inflammatory risk factors in obese women. Therefore, aerobic exercise during fasting can be recommended as an approach to reducing inflammatory risk factors in obesity.